Paradiplomacy of Malang City in Its Efforts to Join the UNESCO Creative Cities Network - Stania Aurelya; Hafid Adim Pradana; Mohd. Agoes Aufiya (ARISTO, 2027)
This research aims to examine the strategies of Malang City in preparing to become a member of the UNESCO Creative Cities Network 2025. Research on Malang City’s paradiplomacy remains limited, offering an opportunity to analyze the local government’s role in international cooperation. Using a descriptive qualitative method, the study applies the paradiplomacy concept as an analytical framework encompassing global paradiplomacy and multipurpose paradiplomacy indicators. The findings reveal that participation in the UCCN strengthens the creative economy, promotes cultural and knowledge exchange, and enhances the city’s international image. Key strategies include infrastructure development, creative human resource capacity building, and the creation of a sustainable collaborative ecosystem. The implementation of these strategies has positioned Malang City as one of the UCCN 2025 members in the Media Arts category. Further studies are recommended to examine the sustainability of Malang City's paradiplomacy through the UCCN by analyzing the extent to which creative programs and policies during the membership period impact the development of the regional creative ecosystem. Keywords: Creative Economy; Creative City; Media art; Paradiplomacy; UNESCO;